Gabapentin's Effects on Hyperemesis Gravidarum: A Randomized Controlled Trial [17N]. (May 2020) - Guttuso, Thomas; Messing, Susan; Mullin, Patrick; Strittmatter, Chad; Saha, Sumona; Thornburg, Loralei Lacina
Abstract : INTRODUCTION: Hyperemesis gravidarum (HG) is a disabling disease of early pregnancy for which there are no effective outpatient therapies. Because of the severe and persistent physical and psychological distress caused by HG, about 15% of HG pregnancies are terminated in the first trimester. METHODS: A randomized, double-blind, multi-center trial was conducted among patients with medically-refractory HG. Subjects were randomized (1:1) to either oral gabapentin (1, 800–2, 400 mg a day) or an active comparator arm of either oral ondansetron (24–32 mg a day) or oral metoclopramide (45–60 mg a day) for 7 days. Change in Motherisk-PUQE scores from baseline to Days 5–7 served as the primary endpoint. RESULTS: Thirty-one patients were enrolled from 10/2014–5/2019. Among the 21 subjects providing any primary outcome data (12 assigned to gabapentin, 9 to the active comparator arm), 18 were enrolled as outpatients and all 21 were outpatients on Days 5–7. Intention-to-treat analysis showed the gabapentin treatment arm to have greater reductions in Motherisk-PUQE scores ( P =.005) and increases in oral nutrition ( P =.007) from baseline as well as higher global satisfaction ( P =.02), relief ( P <.05) and desire to continue therapy ( P =.04) compared to the active comparator arm. Adverse events and number of subject withdrawals were equivalent between the groups. CONCLUSION: Despite the small sample size of this trial and high rate of subject attrition, gabapentin therapy was more effective than standard-of-care therapy for HG symptoms in the outpatient setting. Considering the favorable safety profile of gabapentin use during early pregnancy, gabapentin therapy may be able to provide HG patients and their infants with improved long-term prognoses.